Integration of RS/GIS and community knowledge-based data analysis for scenario modeling of water allocation management in downstream Angat River - Veneracion, Victor John J.
The Angat watershed in Bulacan supplies about 76% of the total domestic water needs of Metro Manila. The Angat dam also contributes about 200MW of hydroelectric power to the Luzon grid. But most people don't realize that the river also provide irrigation to almost 28, 000 hectares of farmlands in Central Luzon. It is also home to a wide variety of aquatic life and a source of livelihood for many living along the river. But since the construction of these dams and rapid urbanization, the Angat River suffered tremendous presseres which ultimately made it dry and polluted. Thus, an integrated water resource management IWRM approach is neede to remove the confussion and chaos caused by the different sector's disputes for water rights. The IWRM approach was formalized by the Technical Committee of the Global Water Partnership in year 2000, which aims to strike a balance between exploiting this finite resource for ensuring the livelihood of an increasing population and to protect and conserve the water resource.